PENINGKATAN KEMAMPUAN MEMBACA BAHASA JERMAN MELALUI PENDEKATAN SCIENTIFIC - Mutmainna Mutmainna; Burhanuddin Burhanuddin (Makassar State University, 2018)
The purpose of this study is to improve the ability to read German through the scientific approach of students class XI IPA SMAN 14 Gowa. This research is a classroom action research. The subjects of this study were students of class XI IPA 3 which amounted to 35 students. This classroom action research consists of two cycles. Each cycle consists of planning, execution, observation, and reflection. Data analysis in this research using percentage technique. The results of this study showed that there is an increase in learning achievement of German reading ability through scientific approach of students.